2006
DOI: 10.7589/0090-3558-42.1.170
|View full text |Cite
|
Sign up to set email alerts
|

A Paretic Condition in an Anaplasma phagocytophilum Infected Roe Deer Calf

Abstract: ABSTRACT:This paper describes a case of Anaplasma phagocytophilum infection in a roe deer (Capreolus capreolus) calf in Norway. The calf was found deserted, paretic, and heavily infested with Ixodes ricinus ticks. It was euthanized and investigated postmortem. Anaplasma phagocytophilum was detected in several tissues by polymerase chain reaction (PCR) and 16S rRNA sequence analyses. Analyses for Borrelia burgdorferi sensu lato and tick-borne encephalitis (TBE) virus infections were negative. This is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…The zoonotic agents found were B. henselae , B. clarridgeiae , B. burgdorferi s. l., R. helvetica and R. monacensis . Contrary to the results of other investigations in Europe, including Italy (Ogden et al., 1998; Favia et al., 2001; Stuen et al., 2002, 2006; Bown et al., 2003; Polin et al., 2004; Mantelli et al., 2006; Piccolin et al., 2006), no DNA of A. phagocytophilum was identified. Bartonella spp.…”
Section: Discussioncontrasting
confidence: 92%
“…The zoonotic agents found were B. henselae , B. clarridgeiae , B. burgdorferi s. l., R. helvetica and R. monacensis . Contrary to the results of other investigations in Europe, including Italy (Ogden et al., 1998; Favia et al., 2001; Stuen et al., 2002, 2006; Bown et al., 2003; Polin et al., 2004; Mantelli et al., 2006; Piccolin et al., 2006), no DNA of A. phagocytophilum was identified. Bartonella spp.…”
Section: Discussioncontrasting
confidence: 92%
“…Though a case of a paretic condition in a young roe deer was attributed to infection with Anaplasma sp. [61], it is generally held that the effect of Anaplasma sp. on red deer is weak (S. Stuen, pers.…”
Section: Discussionmentioning
confidence: 99%
“…In Wisconsin, Michalski et al [39] found a prevalence in ticks between 5.8% and 8.9%, and in white-tailed deer between 11.5% and 26% using PCR and DNA sequencing. A paretic condition in an A. phagocytophilum infected roe deer calf [40] and ehrlichiosis in a moose calf [12] has been observed in Norway. The high level of infected ticks at Fjelløyvær and Strøm (Table 4) not surprisingly shows that roe deer and red deer probably are competent reservoirs and vehicles for this bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only 0.5% of A. flavicollis was A. phagocytophilum positive. Investigations from Switzerland, England and Norway have shown that deer and sheep can be reservoir hosts [14,40,46]. Migrating birds have also been considered important in the dispersal of A. phagocytophilum infected I. ricinus in Europe and in the distribution of HGA [17,38].…”
Section: Discussionmentioning
confidence: 99%